2008
DOI: 10.1183/09031936.00093207
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4-mediated regulatory phenotype of T-cells in tolerant lung recipients

Abstract: Obliterative bronchiolitis (OB) is the major cause of long-term lung allograft loss resulting from an unclear immune process occurring in the absence of the donor's immune cells. The present authors hypothesised that interactions of autologous dendritic cells (DCs) with Tcells could differ in OB patients compared with healthy lung transplant recipients (LTRs).Monocyte-derived DCs from 14 OB and 35 non-OB LTRs were cultured with autologous T-cells. T-regulatory (Treg) cells, co-receptors, cytokine production, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
0
10
1
Order By: Relevance
“…This does not seem to be in line with a report from Botturi and colleagues, who demonstrated that DC generated from BOS patients and stimulated with Pseudomonas aeruginosa extracts expressed less IDO and were less efficient at Treg-cell amplification than DC obtained from stable recipients. 28 However, several differences must be considered when comparing our data and those of Botturi et al, including different culture and stimulation conditions and different methods of IDO expression/activity assessment, which could justify this discrepancy. Nevertheless, data we obtained on IFN-␥-stimulated PBMC seem to suggest that the global increase in IDO activity we detected in BOS plasma should not be ascribed to an increase of enzyme expression by DC.…”
Section: Discussioncontrasting
confidence: 47%
“…This does not seem to be in line with a report from Botturi and colleagues, who demonstrated that DC generated from BOS patients and stimulated with Pseudomonas aeruginosa extracts expressed less IDO and were less efficient at Treg-cell amplification than DC obtained from stable recipients. 28 However, several differences must be considered when comparing our data and those of Botturi et al, including different culture and stimulation conditions and different methods of IDO expression/activity assessment, which could justify this discrepancy. Nevertheless, data we obtained on IFN-␥-stimulated PBMC seem to suggest that the global increase in IDO activity we detected in BOS plasma should not be ascribed to an increase of enzyme expression by DC.…”
Section: Discussioncontrasting
confidence: 47%
“…It could result from the intrinsic defect in the CTLA-4+ and Treg populations as CTLA-4, known to be involved in tolerance induction [22], could prevent the asthmatic inflammation by inducing T cells to differentiate in T regulatory cells. Recently, we have showed during in vivo studies a lower proportion of Treg cells in blood from severe refractory asthmatics compared to controls, which was even deeper during exacerbations, both in blood and induced sputum [9].…”
Section: Discussionmentioning
confidence: 99%
“…Because this early study was cross-sectional in design, it could not account for the fact that patients with BOS may have lower Treg counts as a direct consequence of higher cumulative and mean levels of calcinurin exposure. These findings have subsequently been confirmed by another group in which foxP3 expression was compared in autologous dendritic cell/peripheral blood mononuclear cells (PBMC) co-cultures in patients with BOS and patients with stable lung function [48]. Induction of foxP3 and production of IL-10 was observed in stable patients, whereas these markers were decreased after co-culture in patients with BOS.…”
Section: Tregs As a Biomarker—on The Road To Mechanismmentioning
confidence: 65%